RETRACHED Inhibiting Factors For Sustainable Use (Solid) Of Palm Waste As Food For Beef Cattle In Seluma District - Andi Ishak; Erpan Ramon; Zul Efendi; Emlan Fauzi; Afrizon Afrizon (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
Farmers in oil palm plantation areas in Seluma Regency have utilized the solid potential of palm oil waste as a source of beef cattle feed. Tunas Harapan Livestock Group, Sumber Arum Village, Sukaraja District, started using solid feed in 2009 to 2017, but now many farmers are no longer using it. This study aims to identify the inhibiting factors for solid use in Tunas Harapan Livestock Group. The study was conducted from July to August 2018. Data collection through in-depth interviews involved two key informants, namely the Head of the Farmer's Group and an agricultural extension worker, which was confirmed by interviews with 3 farmers and observations. The data collected is the result of the identification of technical, economic, and social factors related to the maintenance of beef cattle. The data were analyzed using the AHP (Analytical Hierarchy Process) method. The results showed that technical factors were the main obstacle to solid use with a value of 63.7%, followed by economic factors (25.8%) and social factors (10.5%). The reduction in the scale of livestock rearing from 4-5 to 1-2 is the dominant technical factor that hinders the sustainability of solid use in the field.